CPO Bleaching Optimization Using Activated Charcoal And Bentonite - A Abdullah; Yudhistira Abdi Atmanegara; Radna Nurmasari (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2010)
Research of Crude Palm Oil (CPO) bleaching optimization using activated charcoal and bentonite on biodiesel synthesize had been done. The aim of this research is to find optimum condition of bleaching process, by making variation of activated charcoal and bentonite ratio as adsorbent (1:0, 1:10, 1:15, 1:20 and 0:1), temperature (non heated, 40-50oC, 60-70oC, 80-90oC and 100-110oC) and time (1; 1,5; 2; 2,5 and 3 hours). The results of this research will be used as optimal conditions for synthesizing biodiesel. Optimum condition was determined by observing the lowest absorbent which was measured by using spectronic-20 on 445 nm. Results showed that optimum activated charcoal and bentonite adsorbent ratio was 0:1, optimum temperature was 100- 110oC and optimum time was 3 hours.